Bilateral simultaneous thalamic hematomas – Unusual presentation of intracerebral hemorrhage: A case report - Rita Magyar-Stang; Marcell László Palotai; Gertrúd Tamás; Judit Kárpáti; Péter Barsi; Dániel Bereczki; Bence Barna Gunda (Heliyon, 2023)
Background: Bilateral symmetrical simultaneous thalamic hemorrhages are extremely rare. Case presentation: A 52-year-old female patient with a history of untreated hypertension, ischemic heart disease and type 2 diabetes mellitus was admitted with somnolence, disorientation, 3/5 right-sided hemiparesis and blood pressure of 200/110 mmHg. Cranial CT scan showed bilateral thalamic hemorrhages, with bilateral intraventricular propagation and subarachnoid component along the frontal, parietal and occipital lobes. CT angiography did not show any source of bleeding or cerebral vein or sinus thrombosis. Coagulation laboratory parameters were in normal range.The patient was treated with a combination of intravenous and oral antihypertensive medication; five days later she become normotensive with improving motor function but was still somnolent.Six weeks later she was fully alert, motor functions continued to improve, but had severe cognitive deficit. Repeated neuropsychological assessment showed a slow and moderate improvement of a major neurocognitive impairment. At discharge her Mini Mental State Examination score was 13/30 and Addenbrooke's Cognitive Examination III score was 42/100.Cranial MRI scan eight weeks later depicted subacute-chronic stages of the bilateral hemorrhages, regression of perifocal edema, cerebral microbleeds in the left external capsule and the pons.At discharge after 2 months, she was alert, had no focal neurological signs, but was unable to care for herself due to lack of motivation, spatial and temporal disorientation and severe cognitive deficit. Conclusion: Simultaneous bilateral thalamic hemorrhages are extremely rare, the most commonly observed symptom is cognitive impairment. Our case was caused by hypertensive crisis, but in the differential diagnosis, sinus thrombosis, hemorrhagic transformation of ischemic stroke and various hemophilias should be considered.